Seasonal variation in the frequency of anencephalus and spina bifida births in the United Kingdom. Issue 2 (June 1984) - Maclean, M H; MacLeod, A
Abstract : There have been statistically significant seasonal variations of annencephalus and spina bifida in each country of the United Kingdom during 1964-79 with the exception of anencephalus births in Northern Ireland. The seasonal peaks, where discernible, are in phase. Embryos appear to develop anencephalus most commonly in May-June and spina bifida in July.